The Role of Effluent Analysis and Culture in Diagnosis and Monitoring of Peritoneal Dialysis-Related Peritonitis - Nuri Dyah Indrasari; Najib Ali (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Peritoneal Dialysis (PD) is one of the available renal replacement therapy options for End-Stage Renal Disease (ESRD). One of the most common complications of PD is peritonitis. A 13-year-old boy was admitted to the hospital due to cloudy effluent and abdominal pain four days before admission. He was diagnosed with ESRD in 2015 and has undergone Continuous Ambulatory Peritoneal Dialysis (CAPD) since 2017. The physical examination findings were as follows: the temperature was 36.6 C, the conjunctiva was anemic, the abdomen was tender, and both of the lower extremities were edematous. Peritoneal dialysis effluent analysis showed yellow and turbid effluent with a leukocyte count of 13.346 cells/µL and polymorphonuclear (PMN) cells predominance (69.3%), effluent and serum urea of 221 and 243 mg/dL, effluent and serum creatinine of 16.7 and 18.26 mg/dL, respectively. Effluent Gram stain showed increased leukocytes without bacteria, while effluent culture showed the growth of Methicillin-sensitive Staphylococcus aureus. According to the International Society of Peritoneal Dialysis 2022 guidelines, all criteria for infective peritonitis in this patient were met: clinical features (turbid effluent and abdominal pain), increased cell count (>100 cells/µL) with PMN >50%, and positive effluent culture. The patient was administered intravenous Ampicillin-Sulbactam based on the effluent culture and antimicrobial susceptibility testing. Serial effluent analyses suggested a return-to-normal trend in leukocyte and PMN counts. After 18 days of hospitalization, the patient was allowed to discharge based on clinical and laboratory improvements.